Diversidade de elasmobrânquios capturados pela pesca de pequena escala realizada por uma frota de Camocim, litoral oeste do Ceará, Brasil - Saldanha, Thifany Ribeiro (2024)
Half of the elasmobranch species recorded in Brazil can be found along the northeastern coast, and approximately 50% of these species are listed as being under some degree of threat at the national level. Therefore, it is essential to conduct studies on the occurrence and fishing of these species, as this information can help guide their management and conservation. The aim of this study was to characterize the fishing of sharks and rays by a small-scale fishing fleet based in Camocim, Ceará. Landings were monitored from February 2023 to January 2024, on two days per week. All elasmobranch specimens landed were identified to the lowest possible taxonomic level, based on external morphological characteristics. The specimens were quantified by number and total weight, and also recorded by fishing gear (gillnets and handlines). In total, 570 elasmobranch specimens (113 sharks and 457 rays) from 13 taxa were recorded, eight of which were identified at the species level (441 specimens) and five at the genus level (129 specimens). At least 13 elasmobranch taxa are currently caught by the small-scale fishing fleet based in Camocim, with Hypanus guttatus being the most landed, followed by Hypanus berthalutzae and Rhinoptera spp. At least half of these species are at some degree of risk of extinction, according to current Brazilian legislation. These elasmobranchs are caught by the fleet using canoes and waiting nets (53.5%) or canoes and handlines (46.5%).